Performance analysis of FSO with haze attenuation consequence acclimatize in tropical rainforest environment - Mohammad, Zuliyana; Anuar, M. S.; Aljunid, S. A.; Rahman, A. K.; Rashidi, C. B. M.; A Bakar, M.S. (Asian Research Publishing Network (ARPN), 2015)
Free Space Optic (FSO) is an attractive link communication due to its outstanding capability to fulfil rapid demands in today’s technology era. The bandwidth and speed FSO possess is similar to fiber optics.However, FSO is highly preferred than fiber optics.This can be seen in comparing the point of the deployment time frame and cost effectiveness.However, since the atmosphere is the transmission medium for FSO, the connection may be attenuated as atmosphere condition varies.The attenuation is due to climate vulnerability and it will distort the FSO link performance especially rains and haze since this type of weather occurring throughout the year in tropical temperate region.This paper is focused on the analysis of haze attenuation with real visibility data from meteorological departments for the mid-year 2012 until mid-year of 2013 and constructs the tropical haze attenuation model especially the maximum range of FSO system deployment.Here, low and moderate visibility was concentrated more in this research due to worst condition for FSO link. The data used is analysed with theoretical part and simulated using Optisystem software 6.0 version and validated with experimental part (lab scale).Observation performance is characterized through bit error rate (BER) synchronization and power received with related to the link range relationship.